Análise dos impactos da Covid-19 no mercado brasileiro de energia elétrica - Estavare, Fernando Hiratsuka [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
The Covid-19 pandemic significantly changed the national scenario in a sudden way during the beginning of 2020. This current work has the objective to analyze the impacts of this change in the light of the national energy market. In the context of the generation during 2020, there was a reduction of 6.2% in the supply of non-renewable sources and an increase of 2.5% in the supply of renewable sources, when compared to its offers in 2019, with great emphasis for the solar source supply. The solar generation had an increase of 187% in micro and mini distributed generation. The necessary sanitation management to contain the virus and the political and socioeconomic uncertainty caused a frustration of market expectations and a consequent decrease in electricity consumption. The greatest variations on energy consumption in the National Interconnected System, when compared to the same period in 2019, were observed in 2020 in the months of April and May, which had a reduction of 12.1% and 10.9%, respectively. This decrease, together with the economic downturn and the increase in consumer defaults, caused a reduction in distributors' billing, which motivated the creation of the Conta Covid. The account, which comprises a loan coordinated by BNDES with 16 public and private institutions, was responsible for the transfer of R$ 14.8 billion to the affected distributors in the period. Thus, future tariff adjustments were diluted in 60 months and the sector had more liquidity. In the free energy market, the decrease in national energy consumption caused a drop in the Preço de Liquidação das Diferenças (PLD), which, together with the historical situation, exposed its consumers to the short-term market. It is estimated that the differences between contract prices and the short-term PLD caused a loss of R$ 5 billion in the free energy market during the year 2020

A pandemia de Covid-19 alterou significativamente o cenário nacional de forma súbita durante o início do ano de 2020. Este trabalho busca analisar os impactos dessa mudança no contexto do mercado nacional de energia. No campo da geração durante o ano de 2020, verificou-se uma redução de 6,2% na oferta de fontes não renováveis e um aumento de 2,5% da oferta de fontes renováveis, quando comparadas com suas ofertas em 2019, com grande destaque para a oferta de fonte solar. Esta, teve um aumento de 187% de sua geração em micro e minigeração distribuída. As medidas sanitárias necessárias para a contenção do vírus e a incerteza política e socioeconômica causaram uma frustração de expectativas do mercado e consequente diminuição do consumo de energia elétrica. As maiores variações de consumo no Sistema Interligado Nacional, quando comparadas ao mesmo período em 2019, foram observadas nos meses de abril e maio de 2020, que contaram com uma redução de 12,1% e 10,9%, respectivamente. A diminuição do consumo, aliada à retração econômica e ao aumento da inadimplência de seus consumidores, causaram uma redução no faturamento das distribuidoras, o que motivou a criação da Conta Covid. A conta, que compreende um empréstimo coordenado pelo BNDES junto a 16 instituições públicas e privadas, foi responsável pelo repasse de R$ 14,8 bilhões às distribuidoras afetadas no período. Assim, diluiu-se os futuros reajustes tarifários em 60 meses e injetou-se liquidez no setor. No mercado livre de energia, a diminuição do consumo nacional causou uma queda no Preço de Liquidação das Diferenças (PLD) que, junto à conjuntura histórica, expôs seus consumidores ao mercado de curto prazo. Estima-se que as diferenças entre os preços de contrato e o PLD do curto prazo causaram um prejuízo de R$ 5 bilhões no mercado livre de energia durante o ano de 2020.
Analysis of the impact of Covid-19 in the electrical energy brazilian market
Keywords: Pandemic; Electric energy consumption; Covid-19; Pandemia; CDE-Covid; Consumo de energia elétrica; ACR; ACL